Prognostic factors in chronic lymphocytic leukaemia - Lewandowski, Krzysztof; Matuszak, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2003)
Chronic lymphocytic leukaemia (CLL) is the most frequent leukaemia in adults (about 20–30% of all leukemias in the Western world). In the United States, each year about 12,000 new cases are registered. In 90% of the cases the age at diagnosis is over 50–60 years. The frequency of the disease is twice as high in males as compared to females. Chronic B-lymphocytyic leukaemia has a variable clinical course, from a very indolent form to a progressive one. Recently, new prognostic factors have been identified, i.e. serum markers such as LDH, thymidin-kinase, b2-microglobulin, CD 23 and CD 44, IgvH gene status, expression of ZAP-70 and of the CD 38 antigen in neoplastic cells. The presence of cytogenetic abnormalities have also practical significance. In persons with 11q and 17p deletions a rapid progression of the disease is observed. The response to the treatment applied is also poor, with short survival time in comparison to patients without cytogenetic abnormalities or deletion of 17p only. Mentioned laboratory data, independently of Rai’s and Binet’s clinical staging systems, allowed to identify a group of patients with chronic lymphocytic leukaemia with unfavourable outcome of the disease, which should be intensively treated immediately after diagnosis.